2022
DOI: 10.1039/d2gc02169b
|View full text |Cite
|
Sign up to set email alerts
|

A review of biodegradable thermoplastic starches, their blends and composites: recent developments and opportunities for single-use plastic packaging alternatives

Abstract: This review article effectively analyses the effect of multiple plasticizers, compatibilizers, and essential oils on plasticized starch in the preparation of thermoplastic starch-based biodegradable blends and composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 227 publications
(285 reference statements)
0
41
0
Order By: Relevance
“…The first peak at ~61 °C is related the glass transition (Tg) of PLA [ 43 ], the second endothermic peak at ~119 °C corresponds to the melting of PBAT (Tm 1 ), which is found between 115 and 125 °C [ 44 ], and the last peak ~160 °C (Tm 2 ) is related to the melting of PLA [ 39 ]. With respect to the TPS, Surendren and coworkers indicated that the endothermic peaks between 165 °C and 180 °C could belong to the melting temperature (Tm) of thermoplastic starch (TPS) [ 45 ], while other research indicates that TPS has a wide melting range between 160 and 380 °C, which depends on the botanical origin and proportion of the starch the amylose/amylopectin ratio of the starch structure, in addition to the plasticizer used and the plasticizing conditions [ 46 ]. The behavior of Tg, Tm 1 , Tm 2 and Tc is similar to that reported by Bianchi and Morreale (2023).…”
Section: Resultsmentioning
confidence: 99%
“…The first peak at ~61 °C is related the glass transition (Tg) of PLA [ 43 ], the second endothermic peak at ~119 °C corresponds to the melting of PBAT (Tm 1 ), which is found between 115 and 125 °C [ 44 ], and the last peak ~160 °C (Tm 2 ) is related to the melting of PLA [ 39 ]. With respect to the TPS, Surendren and coworkers indicated that the endothermic peaks between 165 °C and 180 °C could belong to the melting temperature (Tm) of thermoplastic starch (TPS) [ 45 ], while other research indicates that TPS has a wide melting range between 160 and 380 °C, which depends on the botanical origin and proportion of the starch the amylose/amylopectin ratio of the starch structure, in addition to the plasticizer used and the plasticizing conditions [ 46 ]. The behavior of Tg, Tm 1 , Tm 2 and Tc is similar to that reported by Bianchi and Morreale (2023).…”
Section: Resultsmentioning
confidence: 99%
“…Sorbitol is known to be the main starch plasticizer used for SBP, and we confirmed this here through GC–MS analysis after derivatization (Figure S6). ,, The elemental analysis of SBP was compared to that of its components (PBAT, starch, and sorbitol) to estimate an average composition. It was found that the SBP consisted of 64% PBAT and 34% starch and sorbitol, as well as 2% inorganic components (Table ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Starch undergoes rapid biodegradation by enzymatic hydrolysis to produce glucose, which is further assimilated to produce CO 2 and H 2 O in compost or soil environments . To process TPS efficiently and to blend and derive good interfacial adhesion between hydrophilic starch and hydrophobic PLA, compatibilizers are generally used. Blending PLA and TPS helps improve the oxygen and water vapor barrier properties and the elongation at break of the resulting matrix . Furthermore, the hydrophilic feature of TPS can enhance PLA’s sensitivity to humid environments and act as an excellent initial nutrient source for the microbes when introduced into the compost environment. …”
Section: Introductionmentioning
confidence: 99%